The economics of Bagòss cheese production in Bagolino, Italy - Marletta, Piercarlo (Kansas State University, 2009)
Many small communities in the Alps are facing the same problem of ensuring a durable economic development, protecting their natural resources and preserving their traditions under the constraints of higher production costs, distance from markets, isolation, severity of climate, a lower level of public services. This is the situation faced by Bagolino, a small town of roughly 4,000 inhabitants located in the Italian Alps. One of the major supporters to the growth of Bagolino, along with tourism, is its cheese Bagòss , whose origin dates back centuries. The Bagòss cheese is a semi-cooked cheese that is produced under strict processing methods that have been practiced for centuries. The Bagòss industry, with its unique organizational system, challenges researchers to investigate what factors are decisive in explaining its success. It is an example of a common situation in the Alps whose products arise from history, traditions and natural environment. This research aims to explain which factors influence the production of the Bagòss cheese and which factors explain differences among producers. Various aspects of interest of the Bagòss industry were examined through a literature review: social and economic situation of Bagolino and history of the town helped to get a better understanding of the background of the industry. The review of literature about entrepreneurship and supply chain was aimed to get a better understanding of the Bagòss industry organization; whereas theories about rural development and sustainable development described the social and environmental context of this production. Last the review of the main economic theories helped to analyze the Bagòss industry from the economic perspectives: monopolistic competition and the resource based view of the firm. Data were collected from multiple sources; the main source of data was a survey of farmers that involved all Bagòss producers. Data from administrative source were important for revision and also furnished data that could not be obtained from farmers. Qualitative interviews with experts were important for checking purposes and for understanding of the social and economic environment in which the Bagòss production takes place. Analytical tools of this thesis were of three different types: qualitative data used mainly to describe the growth medium of Bagòss and to formulate hypotheses to be tested with an econometric model. Statistical analysis provides a complete description of the industry. The Bagòss industry is not characterized by highly diversified use of the land: summer pastures, long term meadows and forests are the three main categories of the use of land. Almost all labor force is made up of family members and relatives. There are a total of 657 adult milking cows involved in the Bagòss production, with an average of 24.33 cows per farm; most farmers process all or part of their cow milk. The main product is the Bagòss cheese. We estimated the production at 146.5 tons of Bagòss. 69% of Bagòss is sold after aging for less than a year. In terms of marketing the most important channels are Bagolino’s retailers, consumers buying directly and retailers located outside Bagolino. According to our estimates EBITDA equals to 1,388 thousand Euro, an average of more than 55 thousand euro per farm. Two factors are able to explain most of the variability in the milk production: the number of workdays in the farm and the total cost of purchased feed. The EBITDA / tons of milk ratio is an indicator of the farm efficiency: the explanatory model for this is based on the operator’s age and level of education, the percentage of Bagòss sold after aging for one year or more, the percentage of Bagòss sold by direct sale to consumers and the size of the herd. Finally, a model able to explain the variability of the EBITDA / work days ratio was built; this ratio is considered to be an indicator of the labor productivity. This model is based on the percentage of Bagòss sold after aging for one year or more, the percentage of Bagòss sold to restaurants and hotels, the total milk production and the cost of rent of pastures. The first three have a positive impact on the dependent variable, whereas the fourth has a negative impact. The last two models show that small farms tend to be less efficient in their use of resources, and also less efficient in the use of labor.
Keywords: Dairy; Cheese; Mountains; Alps; Rural Development; Supply Chain; Business Administration, Management (0454); Economics, Agricultural (0503); Economics, General (0501)